Leaving the Dream Behind: Why the Metaphysics of Consciousness cannot be Unveiled by Conceivability Arguments - Luis Alejandro Murillo-Lara (Problemos)
In this paper, I present a novel objection to Chalmers’s “master argument” against the privileged strategy of ‘type B’ physicalists to account for the explanatory gap (the “phenomenal concepts strategy”). Specifically, I argue that the second horn of the master argument gets wrong why zombies cannot have our epistemic situation with regard to consciousness. Zombies cannot have a kind of mental state that we have. If something must have all of our psychological attributes to share our epistemic situation, then zombies cannot serve the purpose of the second horn of the dilemma. By way of background, I begin by briefly outlining a related argument against physicalism, also advanced by D. Chalmers – the “conceivability argument.” I highlight some of the primary challenges with this argument and present additional criticisms. Finally, through a brief examination of panprotopsychism, I consider what lies ahead if Chalmers’s arguments are conceded. I conclude that the phenomenal concept strategy is a sound explanation for why the conceivability of zombies likely does not imply their metaphysical possibility.